If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + 65 = 7p + 37 Reorder the terms: 65 + 3p = 7p + 37 Reorder the terms: 65 + 3p = 37 + 7p Solving 65 + 3p = 37 + 7p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-7p' to each side of the equation. 65 + 3p + -7p = 37 + 7p + -7p Combine like terms: 3p + -7p = -4p 65 + -4p = 37 + 7p + -7p Combine like terms: 7p + -7p = 0 65 + -4p = 37 + 0 65 + -4p = 37 Add '-65' to each side of the equation. 65 + -65 + -4p = 37 + -65 Combine like terms: 65 + -65 = 0 0 + -4p = 37 + -65 -4p = 37 + -65 Combine like terms: 37 + -65 = -28 -4p = -28 Divide each side by '-4'. p = 7 Simplifying p = 7
| -.9v=-14.4 | | -5*(x+2)=15*(x-6) | | -12x=180 | | 6s-8=22 | | T/2.3=9 | | 9/(x-2)+5=0.5 | | -20=3x+7(2x-15) | | 7n=17.5 | | x/5-1=-4 | | R/-8=13.2 | | 6*(x-2)=18 | | 2s-12=20 | | 6x+7=3x-5 | | 45b=58.5 | | -5x-3y=14 | | 7.8k=-124.8 | | 7s-6=15 | | -5x-107=9x+61 | | M/4.5=-7 | | x+4*9+6=15 | | -5.1x=510 | | 3x+5(6x-16)=85 | | 8x-9=8(x-3) | | 4*(x+2)=3(5-x) | | N+7=-4 | | -29-4x=-8x+59 | | S+1.3=-5.1 | | N+1*2=8 | | B+56.8=90.3 | | 3x^2+15x+1=0 | | -x-2/5=x+1/4+1/5 | | H+5.5=-23.5 |